Penanaman Nilai-Nilai Pendidikan Agama Islam pada Anak Usia Dini melalui Program Hafalan Al-Qur’an - Raihan Siti Zulfa; Arif Hakim (UPT Publikasi Ilmiah Unisba, 2022)
Abstract. The purpose of this study was to determine the program for inculcating Islamic religious values ​​in early childhood through the memorization program of the Qur'an. This research uses a case study method with a qualitative approach. With data collection techniques in the form of observation, interviews, and documentation. The case study method uses a qualitative approach because this research provides an overview and examines programs, processes and activities in greater depth in the field with various data collection procedures over a certain period of time regarding the efforts of teachers in managing religious learning at RA Al-Hidayah Kp. Sutam RT 03 RW 04 Sumbersari Village, Ciparay District, Bandung Regency. The research subjects of teachers at RA Al-Hidayah amounted to 5 people. The results of the research on inculcating the values ​​of Islamic religious education at RA Al-Hidayah include: 1. The program for inculcating Islamic religious education through the program of memorizing the Qur'an consists of: a. Lesson planning b. The concept of learning to memorize the Qur'an c. The purpose of learning to memorize the Qur'an. 2. The process of instilling the values ​​of Islamic religious education in RA Al-Hidayah. 3. The inhibiting factor in the process of inculcating Islamic religious education values ​​through memorizing the Qur'an at RA Al-Hidayah. Abstrak. Tujuan penelitian ini untuk mengetahui program penanaman nilai-nilai pendidikan Agama Islam pada anak usia dini melalui program hafalan Al-Qur’an. Penelitian ini menggunakan metode studi kasus dengan pendekatan kualitatif. Dengan teknik pengumpulan data berupa observasi, wawancara, dan dokumentasi. Metode studi kasus dengan pendekatan kualitatif dikarenakan penelitian ini memberikan gambaran dan mengkaji program, proses dan aktivitas secara lebih mendalam yang ada di lapangan dengan beragam prosedur pengumpulan data selama waktu tertentu mengenai upaya guru dalam pengelolaan pembelajaran agama di RA Al-Hidayah Kp. Sutam RT 03 RW 04 Desa Sumbersari Kecamatan Ciparay Kabupaten Bandung. Subjek penelitian guru di RA Al-Hidayah berjumlah 5 orang. Hasil penelitian penanaman nilai-nilai pendidikan agama Islam di RA Al-Hidayah mencakup: 1. Program penanaman pendidikan agama Islam melalui program hafalan Al-Qur’an terdiri dari : a. Perencanaan pembelajaran b. Konsep pembelajaran menghafal Al-Qur’an c. Tujuan pembelajaran menghafal Al-Qur’an. 2. Proses penanaman nilai-nilai pendidikan agama Islam di RA Al-Hidayah. 3. Faktor penghambat dalam proses penanaman nilai-nilai pendidikan agama Islam melalui hafalan Al- Qur’an di RA Al-Hidayah.